Issues and advances in the early stage diagnosis of osteoarthritis - Brown, C (2010)
With the progress of localized treatment procedures such as unicompartmental knee replacement, chondrocyte implantation and osteochondral grafting, it has become important to develop a means of assessing early stage cartilage and bone degradation. This review outlines the recent advances in arthroscopic tools, and discusses the major problems and issues faced in developing effective assessment methods. The central problem in joint tissue assessment is to discriminate degradation from the wide variation in normal tissue. This discrimination, however, is far from being realized by current methodologies, and is compounded by the difficulty in correlating structural features with pain and mobility in the joint. In response to these findings, an argument is provided for a new direction in quantitative tissue evaluation using an integrated chemical, structural, and functional approach, and the importance of structurefunctionpain relationships. © 2010 World Scientific Publishing Company.